Altered cortical morphology of visual cortex in adults with monocular amblyopia. Issue 5 (10th March 2019) - Lu, Lu; Li, Qian; Zhang, Lianqing; Tang, Shi; Yang, Xubo; Liu, Longqian; Sweeney, John A.; Gong, Qiyong; Huang, Xiaoqi
Abstract : Background: The neural mechanism of amblyopia and its impact on the adult brain remain unclear. This hinders effective treatment for adults with this disease. Purpose: To investigate neuroanatomical differences in cortical morphometry between amblyopic adults and healthy controls, and to explore the structural covariance of abnormal morphometric changes. Study Type: Prospective. Population: Twenty‐one amblyopic adults and 34 healthy controls. Field Strength/Sequence: 3T MRI, T1 ‐weighted, MPRAGE sequence. Assessment: All participants completed ophthalmologic exams to confirm the diagnosis of amblyopia or its absence in the healthy controls, including tests of ocular motility and dilation, fundus exam, autorefraction and synoptophore tests. Cortical volume, thickness, and surface area measurements were obtained using FreeSurfer software. Statistical Tests: Statistical differences of MRI measures between amblyopic adults and healthy controls were identified using a general linear model with intracranial volume and age as covariates. Monte Carlo simulations were used to correct for multiple comparisons. The structural covariance of abnormal morphometric changes and the relationship between morphometric abnormalities and visual acuity of the amblyopic eye were examined. Results: Compared with healthy controls, amblyopic adults showed reduced cortical volume in left lateral occipital cortex, and decreased cortical thickness in bilateral inferior temporal gyrus and left precentral gyrus ( P  < 0.05; Monte Carlo corrected). Structural covariance between cortical volume of left lateral occipital cortex and cortical thickness of right inferior temporal gyrus in amblyopic adults was significantly less than in healthy controls ( z  = 1.73; P  < 0.05). Data Conclusion: Our study identified morphological abnormalities in occipital cortex and in temporal and frontal cortex which are projection fields of visual cortex important for processing of visual form and object location information, and disrupted structural covariance of visual cortex with other brain regions in amblyopic patients. Level of Evidence: 2 Technical Efficacy: Stage 3 J. Magn. Reson. Imaging 2019;50:1405–1412.